ANALISIS PERBEDAAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL MENGGUNAKAN RASIO CAMEL - Novianti, Maya (UNIB Press, 2019)
The purpose of this research is to analyze and to know the difference of financial performance between conventional bank and sharia bank period 2012-2016 using financial ratio proxy (CAMEL). The data used in this research is secondary data obtained from financial reports of Conventional Bank and Sharia Bank. The sample size is 29 Banks, consisting of 20 conventional banks and 9 Syariah banks. Data analysis method used is one way ANOVA difference test.The result of the research shows that there is a significant difference between conventional bank financial performance and financial performance of sharia bank seen from Capital Adequacy Ratio (CAR), Net Profit Margin (NPM) and Loan to Deposit Ratio (LDR). While, the ratio of Return On Risk Asset (RORA) and Return On Asset (ROA) financial performance of conventional Bank and Bank of Sharia could not significant difference.